Autotrophic bacterial production of polyhydroxyalkanoates using carbon dioxide as a sustainable carbon source - Sathiyanarayanan, Ganesan; Esteves, Sandra (Frontiers in Bioengineering and Biotechnology, 2025)
The persistence of fossil fuel-based plastics poses significant environmental challenges, prompting increased research into biodegradable polyhydroxyalkanoate (PHA) polymers derived from cost-effective and sustainable resources. Different microorganisms can produce PHA amongst carbon dioxide (CO2)-assimilating autotrophic organisms, particularly noteworthy in carbon capture and utilization (CCU). Autotrophic bacteria have evolved to utilize either light (photoautotrophy) or inorganic chemicals (chemolithoautotrophy) to capture CO2, which powers their primary and secondary metabolic activities. This review explores the diversity of PHA-producing autotrophs, the metabolic pathways implicated in autotrophic PHA accumulation, and recent progress in photoautotrophs and chemolithoautotrophs regarding PHA synthesis using CO2. Additionally, microbial electrosynthesis for converting CO2 to PHA is also discussed. Genetic engineering strategies are also emphasized for the autotrophic synthesis of PHA. This review also addresses the challenges and prospects for sustainable PHA production using CO2.